Deconstructing the Stigma: A Meta-Analysis of Peer-Led and Community-Based Psychosocial Support Interventions on Quality of Life and Stigma Reduction Among Tuberculosis Patients - Rifki Sakinah Nompo; Wahyuni Maria Prasetyo Hutomo; Adellia Dinanda Setyawardani; Yuliana Baru (Open Access Indonesia Journal of Social Sciences, 2025)
Peer-led psychosocial support interventions represent a potentially transformative approach to addressing the dual burden of diminished quality of life and enacted, anticipated, and internalized stigma among tuberculosis (TB) patients. Evidence from rigorous trials remains inconsistent, warranting a systematic synthesis. A systematic review and meta-analysis following PRISMA 2020 guidelines examined randomised controlled trials, quasi-experimental designs, and observational studies evaluating peer-led or community-based interventions in adults with TB. Searches covered PubMed, EMBASE, Global Health, CINAHL, and regional databases through March 2026. Risk of bias was assessed using study-design-specific tools (RoB 2.0 for RCTs, NOS for observational studies, MRAT for reviews). We conducted separate random-effects meta-analyses for two primary outcomes: quality of life and stigma reduction, using Hedges' standardised mean difference (SMD) with DerSimonian-Laird estimation. GRADE certainty assessment was performed. Twelve effect sizes from seven studies (N=1,449 across primary outcomes, with two contributing systematic reviews) were included. Quality of life improved significantly (k=6, SMD=0.3899, 95% confidence interval [0.2911, 0.4886], p<0.001, I²=0.00%, Tau²=0). Stigma reduction also reached statistical significance (k=6, SMD=−0.4175, 95% CI [−0.5208, −0.3142], p<0.001, I²=0.00%, Tau²=0). The overall pooled estimate across both outcomes was non-significant (SMD=−0.0273, 95% CI [−0.2925, 0.2379], p=0.8399), reflecting outcome-specific effects rather than universal benefit. Sensitivity analyses excluding systematic reviews and by study design confirmed directional consistency. Publication bias assessment (Egger's t=−0.26, p=0.80) revealed no evidence of small-study bias. GRADE ratings: moderate certainty for quality of life (due to design heterogeneity), moderate certainty for stigma reduction. In conclusion, peer-led psychosocial support interventions demonstrate efficacy for both quality of life enhancement and stigma reduction in TB patients. The zero heterogeneity finding (I²=0%) warrants cautious interpretation and suggests consistency despite implementation heterogeneity. Clinical integration requires standardised training, fidelity monitoring, and measurement protocols. Future research must employ larger, multi-country pragmatic trials with mechanistic substudies and long-term follow-up.